Ukształtowanie przednio-tylnych krzywizn kręgosłupa studentów filii AWF w Białej Podlaskiej = Anterior-posterior curvatures of the spine in students from the university of physical education in Biała Podlaska - Górniak, Krystyna; Lichota, Małgorzata (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the study was to determine the size of kyphosis and lumbar lordosis in women and men aged 19-23 with varied body structures. The research, conducted in the academic year of 2017/2018, included 210 students from the University of Physical Education in Biala Podlaska. The Diers formetric III 4D device was used to assess their body postures. Anterior-posterior curvatures of the spine as well as pelvic and torso positions in the sagittal plane were characterized. Body height and weight measurements were used to calculate BMI. The data were analyzed using basic statistical characteristics, Student`s t-test, and Pearson`s linear correlation coefficient.
Keywords: studenci; kifoza piersiowa; lordoza lędźwiowa; budowa ciała; students; thoracic kyphosis; lumbar lordosis; body posture